Anti-angiogenic tyrosine kinase inhibitors and the pathophysiology of their toxic effects: revisiting the treatment of anemia in metastatic cancers - Tai Van Nguyen; Eurydice Angeli; Diaddin Hamdan; Morad El Bouchtaoui; Oanh T. Bui; Feriel Azibani; Rong Shen; He Lu; Kien Hung Do; Anne Janin; Quang Van Le; Guilhem Bousquet (Experimental Hematology & Oncology)
Abstract Background Anti-angiogenic tyrosine kinase inhibitors (TKIs) have become major drugs for the treatment of various cancer types, but with an overall high incidence of severe toxicities, particularly haematological toxicities including severe anemia. Methods We treated C57BL6 mice continuously by gavage for 14 days with either sunitinib, pazopanib, or axitinib. In this study, we set out to decipher the pathophysiological mechanisms of anti-angiogenic TKI haematological toxicity. Results We demonstrated that anti-angiogenic TKIs induced a broad range of toxic effects on normal tissues through a cytotoxic effect on normal endothelial cells. Haematological toxicities were particulary marked with sunitinib. Sunitinib-induced hypoxia through the destruction of normal vessels in the bone marrow mainly affected erythrocyte and myeloid lineages, and this was associated with a blockage in erythrocyte maturation. Althought sunitinib-induced anemia was associated with an adaptative response to systemic hypoxia, we demonstrated that erythropoietin (EPO) concentrations in the total bone marrow of sunitinib-treated mice were significantly lower than in untreated mice. This is coherent with the destruction of microvessels in the bone marrow under sunitinib treatment, preventing circulating EPO from reaching the bone marrow at relevant concentrations. However, we demonstrated an additional effect specific to sunitinib that induced autophagy flux inhibition in erythroid progenitors, with a blockage of erythrocyte maturation, leading to more severe anemia. Conclusions We deciphered the pathophysiology of anti-angiogenic TKI-induced anemia, which we observed to be mainly linked to a direct effect on normal bone-marrow vessels and to autophagy flux inhibition in erythroid progenitors under sunitinib.